Dynamics of changes in motor development depending on the quality in the 3rd month of life - Gajewska, Ewa; Naczk, Mariusz; Naczk, Alicja; Sobieska, Magdalena (Frontiers in Public Health, 2022)
The aim of the study was to show that the quantitative and qualitative motor development from the 3rd month of life is key to achieving milestones and that it may be an early warning signal in children at risk of cerebral palsy (CP). The study population included 93 children (69 born at term). Children were born at week 38 ± 4, the mean body weight was 3,102 ± 814 g. All children were evaluated after reaching the 3rd month of life (quantitative and qualitative assessment), and then the 4.5th, 7th, and 12th of life (quantitative assessment). In case of suspected CP, children were followed until the 18th month, when the diagnosis was confirmed. If at the age of 3 months, a child achieved a quadrangle of support and symmetrical support, then its development at the 4.5th month of life was correct, it would creep, and it would assume a crawl position, then in the final assessment (12th month of life), the child would start to walk. If a child failed to achieve a quadrangle of support and symmetrical support and the dynamics of its development were incorrect, the development would be delayed (12th month of life), or CP would develop. A correct qualitative assessment in the 3rd month of life with a high probability guarantees corrects quantitative development at the 4.5th, 7.5th, and 12th months of life. If the qualitative assessment in the 3rd month of life was very low the child would probably be diagnosed with CP at 18 months.